Pharmacotherapy in pregnancy; effect of ABC and SLC transporters on drug transport across the placenta and fetal drug exposure - Staud, Frantisek; Cerveny, Lukas; Ceckova, Martina (Journal of drug targeting, 2012)
Pharmacotherapy during pregnancy is often inevitable for medical treatment of the mother, the fetus or both. The knowledge of drug transport across placenta is, therefore, an important topic to bear in mind when deciding treatment in pregnant women. Several drug transporters of the ABC and SLC families have been discovered in the placenta, such as P-glycoprotein, breast cancer resistance protein, or organic anion/cation transporters. It is thus evident that the passage of drugs across the placenta can no longer be predicted simply on the basis of their physical-chemical properties. Functional expression of placental drug transporters in the trophoblast and the possibility of drug-drug interactions must be considered to optimize pharmacotherapy during pregnancy. In this review we summarize current knowledge on the expression and function of ABC and SLC transporters in the trophoblast. Furthermore, we put this data into context with medical conditions that require maternal and/or fetal treatment during pregnancy, such as gestational diabetes, HIV infection, fetal arrhythmias and epilepsy. Proper understanding of the role of placental transporters should be of great interest not only to clinicians but also to pharmaceutical industry for future drug design and development to control the degree of fetal exposure.
Keywords: ATP-Binding Cassette Transporters; Animals; biologický transport; Female; lékové interakce; Drug Interactions; ženské pohlaví; Membrane Transport Proteins; membránové transportní proteiny; Placenta; lidé; ABC transportéry; těhotenství; Trophoblasts; Pharmaceutical Preparations; léčivé přípravky; Biological Transport; maternofetální výměna látek; racionální návrh léčiv; komplikace těhotenství; Maternal-Fetal Exchange; Drug Design; Pregnancy Complications; zvířata; Pregnancy; placenta; trofoblasty; Humans